Mycelial growth observation of Pleurotus eryngii (Higher Basidiomycota) In Vitro - Owaid, Mustafa Nadhim; Al-Saeedi, Sajid SS; Abed, Idham Ali (International Journal of Environment, 2016)
Five agro-substrates including date palm fibers (fibrillum), wheat straw, white sawdust and their combinations were investigated to grow Pleurotus eryngii. The longer mycelium complete time within bags was 20 days on sawdust (S4), in contrast, the shorter time for mycelium overgrew was completed after 15 days on date palm fiber (S5). In significant (p<0.05), S5 showed the higher growth intensity level (vigorous growth) than other substrates. Thus use of date palm wastes (S5 medium) may be useful for successfully cultivation king oyster mushroom in farm. International Journal of Environment Vol.5(3) 2016, pp.1-10